Efficacy of posterolateral hip muscles strengthening on patellofemoral pain - Kaur, Ramandeep; Arora, Reena; Arora, Lalit (International Journal of Research in Medical Sciences, 2017)
Background: Patellofemoral pain syndrome (PFPS) is a syndrome characterized by pain or discomfort seemingly originating from the contact of the posterior surface of the patella (back of the kneecap) with the femur (thigh bone). Moderate evidence supports the addition of hip abductor and external rotator strengthening, as well as exercises targeting hip flexion and hip extension. Methods: 30 patients were taken from OPD of Department of Orthopedics, Guru Gobind Singh Medical College and Hospital, OPD of University College of Physiotherapy, Faridkot, Punjab, India. The patients were divided into two groups (15 patients each group). Group A was treated with quadriceps strengthening, Group B were treated with quadriceps strengthening with posterolateral hip strengthening (hip abductors and external rotators). Total treatment duration was 4 weeks. Both the groups were assessed for Pain (visual analog scale [VAS]) and health status (Western Ontario McMaster Universities Osteoarthritis Index [WOMAC]). Follow up was done on 2nd and 4th week. Results: Significant improvements in VAS and WOMAC scores were observed in both groups from 0th-week to 2nd week and 0-week to 4th-week follow-up (P<0.05). Improvements in VAS and WOMAC scores in group B were superior to those in group A at 4-week follow-up (P<0.05). Conclusions: The present study has concluded that both Group A and Group B were effective in the management of patello-femoral pain but statistically it was concluded that Group B is more effective as compared to Group A.